Representation in Steven Universe
XVI, 260 p. 22 illus., 21 illus. in color.
Keywords: This book assembles ten scholarly examinations of the politics of representation in the groundbreaking animated children’s television series Steven Universe. These analyses address a range of representational sites and subjects, including queerness, race, fandom, colonialism, and the environment, and provide an accessible foundation for further scholarship. The introduction contextualizes Steven Universe in the children’s science-fiction and anime traditions and discusses the series’ crucial mechanic of fusion. Subsequent chapters probe the fandom’s expressions of queer identity, approach the series’ queer force through the political potential of the animated body, consider the unequal privilege of different female characters, and trace the influence of anime director Kunihiko Ikuhara. Further chapters argue that Ronaldo allows satire of multiple media forms, focus on Onion as a surrealist trickster, and contemplate cross-species hybridity and consent. Thefinal chapters concentrate on background art in connection with ecological and geological narratives, adopt a decolonial perspective on the Gems’ legacy, and interrogate how the tension between personal and cultural narratives constantly recreates memory.